FEATURES OF THE ADAPTATION PERIOD IN INFANTS BORN OF MOTHERS WITH DISABILITIES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article analyzes the clinical and physiological features of the adaptation period in infants born to mothers with deficiency conditions. Factors influencing the adaptation process in infants have been studied, including maternal nutritional status and perinatal factors. Based on the results, recommendations were developed to improve the adaptation process of babies.